Bleeding Risk with Long-Term Low-Dose Aspirin: A Systematic Review of Observational Studies. - Luis A García Rodríguez; Mar Martín-Pérez; Charles H Hennekens; Peter M Rothwell; Angel Lanas (PLoS ONE)
Background Low-dose aspirin has proven effectiveness in secondary and primary prevention of cardiovascular events, but is also associated with an increased risk of major bleeding events. For primary prevention, this absolute risk must be carefully weighed against the benefits of aspirin; such assessments are currently limited by a lack of data from general populations. Methods Systematic searches of Medline and Embase were conducted to identify observational studies published between 1946 and 4 March 2015 that reported the risks of gastrointestinal (GI) bleeding or intracranial hemorrhage (ICH) with long-term, low-dose aspirin (75-325 mg/day). Pooled estimates of the relative risk (RR) for bleeding events with aspirin versus non-use were calculated using random-effects models, based on reported estimates of RR (including odds ratios, hazard ratios, incidence rate ratios and standardized incidence ratios) in 39 articles. Findings The incidence of GI bleeding with low-dose aspirin was 0.48-3.64 cases per 1000 person-years, and the overall pooled estimate of the RR with low-dose aspirin was 1.4 (95% confidence interval [CI]: 1.2-1.7). For upper and lower GI bleeding, the RRs with low-dose aspirin were 2.3 (2.0-2.6) and 1.8 (1.1-3.0), respectively. Neither aspirin dose nor duration of use had consistent effects on RRs for upper GI bleeding. The estimated RR for ICH with low-dose aspirin was 1.4 (1.2-1.7) overall. Aspirin was associated with increased bleeding risks when combined with non-steroidal anti-inflammatory drugs, clopidogrel and selective serotonin reuptake inhibitors compared with monotherapy. By contrast, concomitant use of proton pump inhibitors decreased upper GI bleeding risks relative to aspirin monotherapy. Conclusions The risks of major bleeding with low-dose aspirin in real-world settings are of a similar magnitude to those reported in randomized trials. These data will help inform clinical judgements regarding the use of low-dose aspirin in prevention of cardiovascular events.